Choline-Based Multi-Ingredient Supplementation Can Improve Explosive Strength during a Fatiguing Task - Matthew Gage (MDPI AG, 2021)
Various choline-based multi-ingredient supplementations (CMS) have been suggested in the current market, but the research is limited. The purpose of this study was to investigate the acute effect of a CMS on physical performance. Fourteen male college football players (20.4 ± 1.0 years) participated in a randomized double-blind crossover experiment separated by 7 days. Subjects were given a CMS or a placebo 60 min before physical performance testing measures, including maximum vertical jumps, maximum voluntary isometric contractions (MVIC), maximal voluntary concentric contractions (MVCC), and fatiguing contractions. Four MVICs and seven sets of two MVCCs at various loads (1 N·m to 60% MVIC torque) were performed with the knee extensor muscles while seated on a dynamometer before and after the fatiguing tasks. During the fatiguing tasks, 120 MVCCs (4 sets × 30 reps) were performed with a load equivalent to 20% MVIC. Twitch interpolation technique was used to assess muscle contractile properties and voluntary activation. No significant differences were seen at baseline between sessions for all testing measures including vertical jump height, strength, power, muscle contractile properties and voluntary activation. Rate of torque development and impulse was higher in supplemental session compared to control session throughout the fatiguing contractions (p = 0.018, p < 0.001, respectively). Acute CMS can improve explosive strength by delaying the onset of fatigue.